Insulin lispro low mixture twice daily vs basal insulin glargine once daily and prandial insulin lispro once daily as insulin intensification strategies in patients with type 2 diabetes: Latin American subpopulation analysis of a randomized trial. Issue 1 (December 2016) - Rojas, Arturo; Sposetti, Georgina; Gross, Jorge; Barbieri, Douglas; Duan, Ran; Linetzky, Bruno; Lana, Janaina; Stempa, Oded; Rodriguez, Angel
Abstract Background This post hoc analysis examined the efficacy and safety of twice-daily insulin lispro low mixture (LM25) and once-daily basal insulin glargine plus once-daily prandial insulin lispro (IGL) in a Latin American subpopulation with type 2 diabetes mellitus (T2DM). Methods A phase 4, randomized, open-label, parallel-arm trial included participants aged 18–75 years with T2DM taking once-daily insulin glargine and stable doses of metformin and/or pioglitazone with glycated hemoglobin (HbA1c) 7.5–10.5 % and fasting plasma glucose ≤121 mg/dL. Participants were randomized 1:1 to receive their stable dose of metformin and/or pioglitazone plus twice-daily LM25 or IGL for 24 weeks. The primary efficacy outcome was change in HbA1c after 24 weeks of treatment. Results from participants in Argentina, Brazil, and Mexico are presented here. Results 162 participants (80 LM25; 82 IGL) with mean ± standard deviation (SD) age = 57.3 ± 9.0 years and body mass index = 31.3 ± 5.2 kg/m2 were included. Mean ± SD change in HbA1c from baseline to week 24 was −1.5 ± 1.0 % (LM25) and −1.1 ± 1.2 % (IGL). At week 24, 35.1 % (LM25) and 31.6 % (IGL) of participants achieved HbA1c <7.0 %. Mean ± SD weight gain from baseline to week 24 was 2.4 ± 2.9 kg in the LM25 group and 1.0 ± 3.1 kg in the IGL group. The mean ± SD rates of total hypoglycemia per year were 18.9 ± 27.3 (LM25) and 21.6 ± 31.1 (IGL). Rates of treatment-emergent adverse events were 46 % (LM25) and 39 % (IGL). Conclusions Our results suggest that both LM25 and IGL are viable treatment options for insulin intensification in Latin American patients with T2DM with suboptimal glycemic control on basal insulin glargine. The safety and tolerability profiles of LM25 and IGL are consistent between this Latin American population and the global trial-level population. Trial registration NCT01175824